Impact of Artificial Intelegence Implementation on Corporate Human Recources - Arnoldova, Alisa (2025)
This thesis examines how artificial intelligence (AI) affects Human Resource Management (HRM) in European businesses, with a comparative case study on two companies with different approaches to HR: GlaxoSmithKline (GSK), a convention-based pharmaceutical company with human-driven HR practices, and ECC AG, a tech-savvy company that embeds AI in various HR functions. Based on sound theoretical foundations and qualitative evidence from expert interviews and organisational analysis, this research examines how AI affects major HR outcomes including recruitment efficiency, candidate fit and quality, staff experience, administrative burden, ethical protection, GDPR compliance, and potential for innovation. The research indicates that ECC AG's AI-based model has considerable advantages in terms of speed, scalability, and predictive planning, while that of GSK has strengths in in-depth decision-making, coaching, and ethical standards. The research surmises that none of these models is superior to all others, rather it suggests a hybrid HR approach that integrates the efficiency of AI with the contextual sensitivity of human judgment. Such an idea is particularly relevant in Europe, as regulatory systems and ethical standards play a major role in implementing AI in HR. Ultimately, the thesis contends that the future of HRM is in human–AI collaboration – a framework that allows organisations to tap into technological innovation without sacrificing fairness, inclusion, and human values that are at the heart of managing the workforce.